Meningkatkan Kompetensi ICT Untuk Guru Agar Proses Pembelajaran Maksimal - Afrisya Ghiyats Risholihati; Hana’ Raihana Sausan; Miftah Maulina Syifa; Nuriyati Nuriyati (Program Studi PGSD Kampus UPI di Serang, 2021)
The teacher does not have a role only to function as someone who facilitates the transfer of knowledge, but at the same time also functions to instill values and build the character of students on an ongoing basis. This dual role causes the teacher's position in the era of ICT advancement. It is easy because the teacher remains the main element in the entire learning/education process. Teachers to be able, professional in their fields, to increase their potential in a sustainable manner updating their knowledge in accordance with the times. Therefore, there is a need for ways to improve the competence of ICT teachers so that learning can run optimally and find out what obstacles occur in improving ICT competence. This research uses the method of literature study or literature study. The results of the study indicate that there are obstacles in increasing ICT competence and to improve ICT skills a teacher must be assisted by other parties such as the role of schools, the role of government, and others.